Pitcher Shoulder: Update Article - Ejnisman, Benno (Thieme Revinter Publicações Ltda., 2021)

(untitled) (Rev Bras Ortop (Sao Paulo))
Most shoulder injuries occur due to repetitive overhead movements. Before studying the treatment of these shoulder injuries, it is paramount that health professionals have an understanding of the etiology of and the underlying mechanisms for shoulder pathologies. The act of overhead throwing is an eloquent full-body motion that requires tremendous coordination from the time of force generation to the end of the pitch. The shoulder is a crucial component of the upper-body kinetic chain, as it transmits force created in the lower body to the arm and hand to provide velocity and accuracy to the pitch.